Klimaschutz und Verkehr im Völkerrecht und im Recht der Europäischen Union: Eine Analyse unter Entwicklung und Einbeziehung der Rechtstechnik steuernder Instrumente - Freudenberger, Jakob Wolfgang (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The thesis analyzes and assesses the steering instruments used in international law and EU law with the aim of climate protection in transport (maritime, air, road, rail). Thus, it not only identifies gaps in the legal regime. It also proposes solutions, the admissibility of which is legally evaluated. In addition, the study develops a legal technique that allows for a selective categorization of steering instruments. In addition, it discusses international and EU climate protection law and attaches greater importance to general principles of international law such as the principle of no-harm. For the first time, it presents in detail the regulation of transport in international and EU law.